Investigation of the Churning Loss Reduction in 2D Motion-Converting Mechanisms - Chuan Ding; Yu Huang; Lichao Zhang; Jian Ruan (Energies, 2021)
In recent years, two dimensional (2D) hydraulic components have significantly flourished. After a brief development introduction of the 2D pump and 2D flowmeter, it could be concluded that the churning loss, which is caused by the rotational motion of 2D motion-converting mechanisms, has an increasing effect on reducing energy losses. This paper first presents a new 2D motion-converting mechanism and introduces its structure and working principles. To compare it with the former 2D motion-converting mechanism, the same working conditions were applied when designing the new one. Afterward, the generated churning loss by the active parts of the mechanism, such as the new rotor, was well studied by establishing a simplified CFD simulation model and was also verified to have a smaller churning loss than that of the former mechanism. As another key simulation result, the influence of the axial motion of the new rotor was found to be negligible for the churning loss even when the rotational speed was high enough. A test rig was subsequently built up to prove the simulation by monitoring the torque at various rotational speeds. As a result, the churning losses that took place in the new 2D motion-converting mechanism were certainly reduced, and the potential reasons for that were analyzed, as shown in the conclusion section.